ANALISIS VEGETASI GULMA PADA BEBERAPA KELAS UMUR ACACIA MANGIUM WILLD. DI HUTAN TANAMAN INDUSTRI (HTI) - Widya Purnama Sari; Ardi Ardi; Siska Efendi (Lambung Mangkurat University-Indonesia, 2020)
This study was conducted to determine the composition of weed vegetation in Acacia mangium plants and to see differences in the composition of weed vegetation in several age classes of Acacia mangium plants in industrial plantations (HTI). This research was conducted in June to August 2018 in the industrial plantation of PT. Bukit Raya Mudisa (BRM) main road Km 13.7, Jorong Lubuk Mansagu, Kenagarian Koto Nan IV Di Bawah, Sub-district IX Koto, Regency Dharmasraya, Province of West Sumatra. The method used in this research is survey method by laying out the plot by purposive sampling in A. mangium gardens that are 2, 3 and 4 years old. At each age of the plant 2 observation plots were made measuring 40m × 40m in the plot. There were observational sub-plots measuring 1m ×1m in 10 plots of observation on a diagonal line with a total of 60 plots of observation. Based on the results of the analysis, there were 15 species belonging to 10 families. The number of weed species found in class 2, 3 and 4 respectively were 11, 9 and 11 species. The family of weeds that have the most species is the family Poaceae. Weeds are dominant under A. mangim plantations age 2, namely A. gangetica (38.26%), P. crinitum (14.81%) and I. cylindica (14.37%), almost the same as weeds under A.mangium plantations age 3 years namely A. gangetica (31.54%), A. compressus (20.49%), A.sessilis (19.50%), and P. crinitum (14.41%). The dominant age of 4 years weeds are A.gangetica (43.11%), A. sessilis (15.50%), and P. crinitum (15.36%). Weeds that dominate the A.mangium plantations are included in the group of broad-leaved weeds, so weed control is recommended in A. mangium plantations against broadleaf weeds.